PERTANGGUNGJAWABAN HUKUM PEJABAT PEMBUAT KOMITMEN (PPK) DALAM PENGADAAN BARANG/JASA PEMERINTAH - Naony Fenti Istiqlallia; Raissa Ardelia; Pramudya Ramadhanti (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2020)
Ketidakjelasan hukum Pejabat Pembuat Komitmen (PPK) terkait pertanggungjawaban hukum atas penyimpangan dalam pengadaan barang/jasa pemerintah, yang menimbulkan ketidakadilan hukum berdasarkan Peraturan Pemerintah tentang Pengadaan Barang/Jasa, terlihat bahwa dalam proses pengadaan barang/jasa, tidak hanya melibatkan PPK saja namun juga ada pihak lain yang berperan dalam pengadaan barang/jasa yang saling berkaitan yaitu PA dan KPA. Jurnal ini akan membahas mengenai kedudukan KPA dalam kontrak pengadaan barang/jasa; tanggung jawab pribadi PPK; batas tanggung jawab PPK. Penelitian ini adalah penelitian normatif. Hasil dari penelitian ini kedudukan PPK dalam kontrak pengadaan barang/jasa pemerintah dimulai dari menetapkan rancangan kontrak, mengendalikan Kontrak dan penyelesaian Kontrak. Sehingga PPK turut bertanggungjawab terhadap tuntutan jika terjadi kesalahan. Tanggung jawab pribadi PPK dalam pengadaan barang/jasa pemerintah adalah tanggung jawab pribadi yang timbul atas tindakan maladministrasi PPK dalam penggunaan wewenang sebagai pejabat pelaksana dan tindakan maladministrasi tersebut melahirkan tanggung jawab pidana. Sedangkan tanggung jawab jabatan PPK dalam pengadaan barang/jasa pemerintah adalah tanggung jawab keabsahan (legalitas) penggunaan wewenang dalam pengadaan oleh PPK yang bertumpu pada wewenang, prosedur dan substansi, dan melahirkan tanggung gugat pemerintah/negara.Legal ambiguity of Commitment Making Officials (PPK) related to legal responsibility for irregularities in the procurement of government goods/services, which causes legal injustice based on Government Regulations on the Procurement of Goods/Services, it is seen that in the process of procuring goods/services, it does not only involve PPK but also exists other parties that play a role in the procurement of goods/services that are interrelated, namely PA and KPA. This journal will discuss the position of KPA in the goods/services procurement contract; PPK personal responsibility; KDP’s limit of responsibility. This research is a normative study. The results of this research are the position of PPK in government procurement contracts of goods/services starting from determining the contract design, controlling the contract and contract completion. So that the PPK is also responsible for the charges if something goes wrong. PPK’s personal responsibility in the procurement of government goods/services is personal responsibility that arises from the PPK’s maladministration in the use of authority as an executing officer and the maladministration act creates criminal responsibility. Meanwhile, the responsibility of the PPK position in the procurement of government goods/services is the responsibility of legality (legality) of the use of authority in procurement by PPK which rests on the authority, procedure and substance, and creates accountability for the government/state.